КРУЖКОВАЯ РАБОТА ПО ИНОСТРАННОМУ ЯЗЫКУ КАК ПОЛОЖИТЕЛЬНЫЙ ФАКТОР ФОРМИРОВАНИЯ СОЦИОКУЛЬТУРНОЙ КОМПЕТЕНЦИИ - Садуллаева, А.Н.; Реймбаева, А.А. (SCIENCE and SOCIETY, 2016)
The article deals with the club work in learning foreign languages as the main factor of developing sociocultural competence / awareness of the students at general educational schools. The club work increases the students‘ motivation to the study of a foreign language and develops their creative abilities.